Dig dig digging - Mayo, Margaret; Ayliffe, Alex (New York : Scholastic, 2002)
Simple rhymes introduce various large vehicles, such as dump trucks, fire engines, and tractors, and describe the work that they do.
K
"Originally published in England in 2001 by Orchard Books"--T.p. verso
b
b
Keywords: Motor vehicles -- Juvenile literature; Motor vehicles; Technology